2021
DOI: 10.1152/physrev.00024.2020
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy and COVID-19

Abstract: There are many unknowns for pregnant women during the COVID-19 pandemic. Clinical experience of pregnancies complicated with infection by other coronaviruses e.g. SARS and MERS, has led to pregnant woman being considered potentially vulnerable to severe SARS-CoV-2 infection. Physiological changes during pregnancy have a significant impact on the immune system, respiratory system, cardiovascular function and coagulation. These may have positive or negative effects on COVID-19 disease progression. The impact of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
560
0
97

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 579 publications
(664 citation statements)
references
References 135 publications
(167 reference statements)
7
560
0
97
Order By: Relevance
“… 24 , 25 Following infection and replication within cells infected with SARS-CoV-2, pyroptosis (inflammation-mediated programmed cell death in response to a pathogenic stimulus) occurs, releasing damage-associated molecular proteins and stimulating a pro-inflammatory response. 26 T cells are attracted to the site of infection; however, as the response is modulated in the context of pregnancy, altered clearance of infected cells may favor severe disease.…”
Section: Discussionmentioning
confidence: 99%
“… 24 , 25 Following infection and replication within cells infected with SARS-CoV-2, pyroptosis (inflammation-mediated programmed cell death in response to a pathogenic stimulus) occurs, releasing damage-associated molecular proteins and stimulating a pro-inflammatory response. 26 T cells are attracted to the site of infection; however, as the response is modulated in the context of pregnancy, altered clearance of infected cells may favor severe disease.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of pregnancy on susceptibility to SARS-CoV-2 infection is unclear 22 ; however, comparisons of infected pregnant women with non-pregnant women of the same age suggests that a similar proportion of infections become symptomatic 23 . This would suggest a similar proportion of pregnant and non-pregnant women mount a protective antibody response and seroprevalence estimates are generalisable to non-pregnant women of the same age.…”
Section: Discussionmentioning
confidence: 99%
“…In high income countries, a number of seroprevalence studies have indicated that the proportion of pregnant women who have been infected by SARS-CoV-2 is much greater than the cumulative prevalence identified by PCR testing of symptomatic individuals; seroprevalence estimates range from 5-20% but samples differ in time since the virus first emerged [15][16][17][18][19][20][21] . It remains unclear whether pregnancy alters susceptibility to SARS-CoV-2 infection 22 ; however, a large systematic review has found no difference in risk of becoming symptomatic when comparing pregnant women with confirmed SARS-CoV-2 infection with women of the same age 23 .…”
Section: Introductionmentioning
confidence: 99%
“…An analysis of the WAPM study on COVID-19 reported that early gestational age at infection, maternal ventilatory supports and low birthweight are the main determinants of adverse perinatal outcomes in fetuses with maternal COVID-19 infection ( 300 ). However, significant neonatal respiratory diseases appear to be rare in presence of SARS-CoV-2 positivity ( 301 ). In this context, the key question is whether SARS-CoV-2 can be transmitted to fetuses from a woman infected with COVID-19.…”
Section: Sars-cov-2 Clinical Implication and Potential Mutual Interacmentioning
confidence: 99%